Reunderstanding and significance of high-quality reservoirs of the inner Dengying Formation in the Anyue Gas Field - Xiaofeng Dai; Benqiang Du; Ming Zhang; Jun Li; Tingke Tang; Youping Xu; Lideng Gan; Xiping Sun (Natural Gas Industry B, 2020)
The overall development of the top of the gas reservoir of the Dengying Formation, Upper Sinian in the Anyue Gas Field of the Sichuan Basin, has been deployed, and the inner Dengying Formation is the next potential succession layer. However, the high-quality reservoirs of inner Dengying Formation are undeveloped and cannot be identified on the seismic profiles, which restricts its deepened understanding, exploration and development. In this paper, the logging and seismic response characteristics of high-quality reservoirs were analyzed using the mud logging and well logging data of the Anyue Gas Field, and a seismic response model for high-quality reservoir was established by means of seismic forward modeling. Then, the target processing was carried out for the problem of weak effective signals. Finally, the plane distribution of high-quality reservoirs of inner Dengying Formation and the favorable exploration areas were predicted. And the following research results were obtained. First, there are two types of high-quality reservoirs inside the Dengying Formation, i.e., concentrated vug type and independent cave type. Vertically, the independent cave reservoirs are mainly distributed within 100 m above the mudstone floor of the third Member of Dengying Formation. Horizontally, karst zones are developed along the bed. Laterally, they are scattered and beaded. And the scale is small. Second, seismic response of high-quality reservoirs inside the carbonate rocks is characterized by single-peak concealed “beaded” reflection, whose peak energy is relatively weak and can be easily covered by the noise of seismic data. Third, deep-seated weak signal recovery and processing technology can be used to deal with the weak seismic response of high-quality cave reservoirs, improve the amplitude preservation and S/N ratio of seismic data, and obtain the beaded reflections on seismic profiles so as to realize effective identification of high-quality cave reservoirs. In conclusion, the deep-seated weak signal recovery and processing technology is proved to be operable because the achieved results conform to the drilling data and the seismic forward modeling conclusions. In addition, high-quality cave reservoirs are developed at the bottom of the fourth Member of Dengying Formation, and they are locally distributed in a large scale. Therefore, it's one of the favorable succession layers for the following natural gas exploration and development of the Anyue Gas Field. Keywords: Sichuan Basin, Anyue Gas Field, Late Sinian, Inner Dengying Formation, High-quality reservoirs, Cave, Beaded reflection, Multiple wave, Weak signal recovery, Succession layer series